2011
DOI: 10.4103/1596-3519.82074
|View full text |Cite
|
Sign up to set email alerts
|

Duration of labor with spontaneous onset at the University of Ilorin Teaching Hospital, Ilorin, Nigeria

Abstract: Interestingly, duration of labor was not significantly different among multiparas and nulliparas although it was shorter. Correlation existed between duration of labor and maternal age and individual parity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Additionally, various tissues, organs and factors are involved in the process of parturition; this includes endocrine and paracrine signaling by the mother and the fetus, involving hormones secreted from the placenta, fetal membranes, uterus, decidua and other adjacent tissues, cytokines produced in the uterus, and smooth muscle cell membrane receptors. Alterations in these signaling mechanisms ultimately induce contraction of the uterine smooth muscle, leading to parturition ( 3 6 ). This evidence suggests that uterine smooth muscle contraction is a crucial trigger of the childbirth process.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, various tissues, organs and factors are involved in the process of parturition; this includes endocrine and paracrine signaling by the mother and the fetus, involving hormones secreted from the placenta, fetal membranes, uterus, decidua and other adjacent tissues, cytokines produced in the uterus, and smooth muscle cell membrane receptors. Alterations in these signaling mechanisms ultimately induce contraction of the uterine smooth muscle, leading to parturition ( 3 6 ). This evidence suggests that uterine smooth muscle contraction is a crucial trigger of the childbirth process.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the rate of oxytocin for labor augmentation, 41 studies were eligible, including either all women in labor, 16 , 22 , 33 , 34 , 40 , 41 , 42 , 43 vaginal births only, 9 , 31 , 37 , 39 , 44 , 45 , 46 women with uncomplicated singleton cephalic pregnancies at term, 11 , 17 , 18 , 19 , 32 , 35 , 38 , 47 , 48 , 49 , 50 , 51 or other criteria. 36 , 52 , 53 , 54 Data collection methods were by nonvalidated medical records, 11 , 16 , 17 , 19 , 28 , 32 , 33 , 40 , 41 , 42 , 43 , 45 , 46 , 51 , 54 clinical observations, 9 , 18 , 28 , 31 , 34 , 35 , 36 , 37 , 38 , 48 , 49 , 50 , 53 questionnaires, ...…”
Section: Resultsmentioning
confidence: 99%
“… 36 , 52 , 53 , 54 Data collection methods were by nonvalidated medical records, 11 , 16 , 17 , 19 , 28 , 32 , 33 , 40 , 41 , 42 , 43 , 45 , 46 , 51 , 54 clinical observations, 9 , 18 , 28 , 31 , 34 , 35 , 36 , 37 , 38 , 48 , 49 , 50 , 53 questionnaires, 44 or interviews with women, 39 , 47 whereas 4 studies had no methods described. 18 , 23 , 29 , 52 Studies reported up to 24% missing data. 30 , 33 , 45 , 46 Figure 2 presents average rates of oxytocin for labor augmentation in each country in studies after the year 2000.…”
Section: Resultsmentioning
confidence: 99%